Inovasi Agroteknologi Berbasis Iot Untuk Monitoring Kualitas Tanah Dan Air - * Sastiani (CV. SINAR HOWUHOWU, 2025)
The development of Internet of Things (IoT) technology offers new opportunities in modern agriculture, particularly for monitoring soil and water quality. This study aims to evaluate the effectiveness of IoT systems in monitoring critical agricultural environmental parameters, such as soil moisture, pH, nutrient content, and water quality. The research methodology combines automatic sensor measurements, laboratory analysis, and socio-economic surveys of farmers. The results indicate that IoT systems can provide accurate real-time data, improve the efficiency of water and fertilizer use, and support data-driven decision-making. The implementation of this technology has the potential to increase crop productivity by up to 15% and promote sustainable farming practices. Therefore, IoT-based agrotechnology innovation is a key strategy to address modern agricultural challenges and maintain environmental sustainability.